Transient recombinant expression of highly immunogenic CagA, VacA and NapA in Nicotiana benthamiana - Rambod Barzigar; Mohammad Javad Mehran; Nanjundappa Haraprasad; Basaralu Yadurappa Sathish Kumar; Bashasab Fakrudin (Biotechnology Reports, 2022)
Interest in the plant-based transient production of recombinant immunogenic antigens has tremendously progressed because plants are cost-effective, easily selectable, free of mammalian contamination, and support complex post-translational modifications. Nicotiana benthamiana is a convenient system for transient expression of recombinant antigens. The present study documented a platform for rapid production of Helicobacter pylori CagA, VacA and NapA antigens three days (first harvest, FH) and six days (second harvest, SH) after agro-infiltration using a syringe. In this study, CagA, VacA and NapA antigen genes from Helicobacter pylori were cloned into the binary vector pBI121 and transformed into Nicotiana benthamiana by the Agrobacterium-mediated process. Leaves of four to five weeks old Nicotiana benthamiana plants were agroinfiltrated with EHA105 subtype of Agrobacterium tumefaciens strain containing cloned CagA (pBI121-CagA), VacA (pBI121-VacA) and NapA (pBI121-NapA) constructs. The transient expression and accumulation of the recombinant genes containing CagA, VacA and NapA expression cassettes were confirmed using qRT-PCR by comparing the relative expression at FH and SH post-infiltration with the non-infiltrated (control) samples and using ELISA at 1/5 and 1/10 dilution ratios. The qRT-PCR findings showed that Agrobacterium-mediated syringe infiltration of leaves of four to five weeks old Nicotiana benthamiana plants produced significantly higher transcript levels of CagA (about 8-fold and 7-fold), VacA (38-fold and 24-fold) and NapA (7-fold and 5-fold) genes at FH and SH compared to the control sample. Besides, the maximum amount of CagA, VacA and NapA antigens were detected at the FH stage compared to the SH stage, when the antibody concentrations of the agro-infiltrated leaf extracts containing these recombinant antigens were diluted in a 1/5 ratio. This study has developed evidence to support that recombinant CagA, VacA and NapA can be transiently produced in Nicotiana benthamiana plants.